2018
DOI: 10.1002/mp.12948
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the active volumes of solid‐state photon‐beam dosimetry detectors using the PTB proton microbeam

Abstract: The PTB microbeam facility was used to analyze the diameters and thicknesses of the active volumes of photon dosimetry detectors for the first time. A new method of determining the thickness values with an uncertainty of ±10% was applied. The results appear useful for further consolidating detailed geometrical knowledge of the solid-state detectors investigated, which are used in clinical small-field photon-beam dosimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 16 publications
(38 reference statements)
3
17
0
Order By: Relevance
“…The thickness t of the active volume of the microSilicon detector was measured using the method developed in the previous study, based on the following equation:t=I·Wn·S·ewhere I represents the detector current, W the energy expenditure per electron released in the silicon material (W = (3.6 ± 0.1) eV), n the proton rate, S the energy‐dependent proton stopping power in the active detector volume, and e represents the elementary charge.…”
Section: Methodsmentioning
confidence: 99%
“…The thickness t of the active volume of the microSilicon detector was measured using the method developed in the previous study, based on the following equation:t=I·Wn·S·ewhere I represents the detector current, W the energy expenditure per electron released in the silicon material (W = (3.6 ± 0.1) eV), n the proton rate, S the energy‐dependent proton stopping power in the active detector volume, and e represents the elementary charge.…”
Section: Methodsmentioning
confidence: 99%
“…The same correction can be applied to the mD detector by considering that its polarity, that is, the type of charge carriers being collected, can be changed by reversing the contact connected to the electrometer. Figure (left insert) shows an x‐ray image of the mD detector (adopted from Poppinga et al …”
Section: Methodsmentioning
confidence: 99%
“…). The diamond chip with the sensitive diamond layer (1–2 μm thick) defined by the Schottky contact is shown as a green line. The type of charge carriers, that is, positive or negative, collected depends on which detector's contact (blue or red) is connected to the electrometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…obtained by assuming a smaller effective collecting volume of the detector than the manufacturer‐specified physical volume. In the meantime, it has been demonstrated experimentally, however, that the manufacturer‐specified physical volume of the detector is correct, but recent work has also shown that photon scatter induced by the large metallic contacts in the vicinity of the diamond chip yields a substantial detector signal . It is plausible that the photon scatter by these metallic contacts has a similar perturbation effect as a reduction in the effective collecting volume.…”
mentioning
confidence: 99%